Determination of cadmium in some vegetables produced in the area near the lead and zinc smelting plant in Veles, Macedonia - Stafilov, Trajče; Jordanovska, Vera (Macedonian Journal of Ecology and Environment, 1996)
The occurrence of cadmium in soils samples and some vegetables (onion, lettuce, cabbage, carrot, spinach, gherkin, leek) produced in the area near the lead and zinc smelting plant in Veles city, Macedonia has been presented. The determination of cadmium was performed by atomic absorption spectrometry. The results from the cadmium content in the soil and vegetable samples taken from the different distances of the smelting plant (1,1 5 and 3 km) are compared. The concentration of cadmium in the soil samples which are near to the PbZn smelter is higher than in the samples which are far-away from the smelter. From the results of the investigations it can be also concluded that the cadmium concentration in vegetable samples depends from the distance of kitchen-gardens from the smelting plant. It was found that the content of cadmium in some leafy vegetables is higher than in the other. It is also found evident differences in the cadmium concentrations in washed and unwashed vegetable samples. In the most of the investigation vegetables the content of cadmium is higher than those permitted by Macedonian government regulations (maximum 0.05 mg/kg).